Influence of modified two-stage mixing approaches on recycled aggregate treated with a hybrid method of treatment. Issue 3 (3rd July 2022) - Verma, Abhishek; Babu, Velaga Sarath; S., Arunachalam
ABSTRACT: The depletion of natural resources occurs at a rapidly decreasing rate due to the growing demand for concrete. Therefore, the current research study uses recycled aggregate (RA) in concrete as a replacement for natural aggregate (NA) after proper treatment. The fresh, hardened, and durability properties have been examined in the current work. The adherent mortar over recycled aggregate (RA) makes it lower grade due to increased water absorption and lower strength. Based on Literature, natural aggregate concrete (NAC) has better strength and durability properties than recycled aggregate concrete (RAC). While making concrete using RA, using a two-stage mixing approach (TSMA) improves RAC properties better than the normal mixing approach (NMA). This study examines the influence of different mixing methods on concrete made from treated recycled aggregate(TRA). Four different mixing variants (viz. NMA, TSMA, TSMA1, TSMA2) were used in this work. The natural aggregate (NA) was replaced with TRA at various replacement levels in all variants, including 0%, 25%, 50%, 75%, and 100% in a control mix of M40. Based on the experimental results, the mixing method TSMA2 improved the various properties like strength and interfacial transition zone (ITZ) of TRA concrete compared to all other mixing techniques considered.